Endothelial Dysfunction and Diabetic Cardiomyopathy - Wang, Moran; Li, Yongsheng; Li, Sheng; Lv, Jiagao (Frontiers in Endocrinology, 2022)
The cardiovascular complications contribute to a majority of diabetes associated morbidity and mortality, account for 44% of death in those patients with type 1 diabetes mellitus (DM) and 52% of deaths in type 2 DM. Diabetes elicit cardiovascular dysfunction through 2 major mechanisms: ischemic and non-ischemic. Non-ischemic injury is usually under-recognized although common in DM patients, and also a pathogenic factor of heart failure in those diabetic individuals complicated with ischemic heart disease. Diabetic cardiomyopathy (DCM) is defined as a heart disease in which the myocardium is structurally and functionally abnormal in the absence of coronary artery disease，hypertensive, valvular, or congenital heart disorders in diabetic patients, theoretically caused by non-ischemic injury solely. Current therapeutic strategies targeting DCM mainly address to the increased blood glucose levels, however, the effects on heart function are disappointed. Accumulating data indicate endothelial dysfunction plays a critical role in the initiation and development of DCM. Hyperglycemia, hyperinsulinemia, and insulin resistance cause the damages of endothelial function, including barrier dysfunction, impaired nitric oxide (NO) activity, excessive reactive oxygen species (ROS) production, oxidative stress, and inflammatory dysregulation. In turn, endothelial dysfunction promotes to impaired myocardial metabolism, intracellular Ca2+ mishandling, endoplasmic reticulum (ER) stress, mitochondrial defect, accumulation of advanced glycation end products, and extracellular matrix (ECM) deposit, leads to cardiac stiffness, fibrosis, and remodeling, eventually results in cardiac diastolic dysfunction, systolic dysfunction, and heart failure. While endothelial dysfunction is closely related to cardiac dysfunction and heart failure seen in DCM, clinical strategies for restoring endothelial function are still missing. This review summarizes the timely findings related the effects of endothelial dysfunction on disorder of myocardium as well as cardiac function, provides mechanical insights in pathogenesis and pathophysiology of DCM developing, and highlights potential therapeutic targets.